A Systematic Literature Review of Neuroimaging of Psychopathic Traits - Johanson, Mika; Vaurio, Olli; Tiihonen, Jari; Lähteenvuo, Markku (Frontiers in Psychiatry, 2020)
Introduction: Core psychopathy is characterized by grandiosity, callousness, manipulativeness, and lack of remorse, empathy and guilt. It is often comorbid with conduct disorder and antisocial personality disorder (ASPD). Psychopathy is present in forensic as well as prison and general populations. In recent years, an increasing amount of neuroimaging studies has been conducted in order to elucidate the obscure neurobiological etiology of psychopathy. The studies have yielded heterogenous results and no consensus has been reached. Aims: This study systematically reviewed and qualitatively summarized functional and structural neuroimaging studies conducted on individuals with psychopathic traits. Furthermore, this study aimed to evaluate whether the findings from different MRI modalities could be reconciled from a neuroanatomical perspective. Material and Methods: After the search and auditing processes, 118 neuroimaging studies were included in this systematic literature review. The studies consisted of structural, functional and diffusion tensor MRI studies. Results: Psychopathy was associated with numerous neuroanatomical abnormalities. Structurally, gray matter anomalies were seen in frontotemporal, cerebellar, limbic and paralimbic regions. Associated gray matter volume (GMV) reductions were most pronounced particularly in most of the prefrontal cortex, and temporal gyri including the fusiform gyrus. Also decreased GMV of the amygdalae and hippocampi as well the cingulate and insular cortices were associated with psychopathy, as well as abnormal morphology of the hippocampi, amygdalae and nucleus accumbens. Functionally, psychopathy was associated with dysfunction of the default mode network, which was also linked to poor moral judgment as well as deficient metacognitive and introspective abilities. Secondly, reduced white matter integrity in the uncinate fasciculus and dorsal cingulum were associated with core psychopathy. Thirdly, emotional detachment was associated with dysfunction of the posterior cerebellum, the human mirror neuron system and the Theory of Mind denoting lack of empathy and persistent failure in integrating affective information into cognition. Conclusions: Structural and functional aberrancies involving the limbic and paralimbic systems including reduced integrity of the uncinate fasciculus appear to be associated with core psychopathic features. Furthermore, this review points towards the idea that ASPD and psychopathy might stem from divergent biological processes